2006
DOI: 10.1111/j.1742-7843.2007.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Kolaviron Ameliorate Di‐n‐Butylphthalate‐Induced Testicular Damage in Rats

Abstract: The present study was carried out to evaluate the ameliorative effects of kolaviron (a biflavonoid from the seeds of Garcinia kola ) and curcumin (from the rhizome, Curcuma longa L.) on the di-n-butylphthalate (DBP)-induced testicular damage in rats. Administration of DBP to rats at a dose of 2 g / kg for 9 days significantly decreased the relative testicular weights compared to the controls, while the weights of other organs remained unaffected. Curcumin or kolaviron did not affect all the organ weights of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 32 publications
(45 reference statements)
8
89
0
1
Order By: Relevance
“…DBP dosed at 250, 500 and 2,000 mg/kg also markedly decreased the testicular GSH level, along with degeneration of the seminiferous tubules (Zhou et al, 2010). The DBP-induced injuries in biochemical, spermatological parameters and histological structure of testis could be recovered by treatment with kolaviron or curcumin which have antioxidative activity (Farombi et al, 2007). In addition, pathological levels of ROS are known to cause apoptosis of spermatozoa, resulting in cell death and a reduced sperm count (Agarwal et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…DBP dosed at 250, 500 and 2,000 mg/kg also markedly decreased the testicular GSH level, along with degeneration of the seminiferous tubules (Zhou et al, 2010). The DBP-induced injuries in biochemical, spermatological parameters and histological structure of testis could be recovered by treatment with kolaviron or curcumin which have antioxidative activity (Farombi et al, 2007). In addition, pathological levels of ROS are known to cause apoptosis of spermatozoa, resulting in cell death and a reduced sperm count (Agarwal et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Protective effects of curcumin have been reported in oxidative damage induced by (Ilbey et al 2009;El-Demerdash et al 2009), and aflatoxin-induced biochemical changes and ischemia-reperfusion injury in rat testis (Mathuria and Verma 2007;Wei, Yan, and Zhou 2009). It has been reported that curcumin recovers the histological structure of the testis after di-nbutylphthalate-induced testicular damage (Farombi et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, the principal component of the curry spice turmeric (Curcuma longa) used in many parts of the world as a spice and medical agent possesses anti-oxidant properties and has no toxic effects. [2][3][4][5] Gal acids are added to foods to prevent oxygen-induced lipid peroxidation as a result of its antioxidant properties. 6,7 However, the potential of Gal to function as antioxidant may be dependent on the dose and their molecular polarities, which could account for the controversial function of Gal as an antioxidant and pro-oxidant molecule.…”
Section: Introductionmentioning
confidence: 99%